Moderating Factors Affecting Brand Loyalty In Boycotts of Israel-Affiliated Brands - Nurdiani, Anggi (Journal of Consumer Studies and Applied Marketing, 2024)
This study explores how brand loyalty influences Indonesians' decisions to boycott brands associated with Israel following a significant event in October 2023 that renewed global attention on the Palestine-Israel conflict. Employing a mixed-method approach, the research integrated qualitative interviews and quantitative surveys with 546 respondents, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that brand loyalty significantly negatively affects boycott behavior, indicating that consumers with high brand loyalty are less likely to engage in boycotts. However, perceived efficacy notably moderates this relationship, as those who believe their boycott actions are effective are more likely to participate in boycotts despite their brand loyalty. In contrast, animosity, subjective norms, and counter-arguments do not significantly impact the connection between brand loyalty and boycott intentions. These findings underscore the intricate interplay between brand loyalty and consumer activism, providing valuable insights for brands addressing ethical dilemmas. To navigate political and social issues effectively, brands should strive for neutrality and uphold ethical practices to mitigate the influence of such issues on consumer behavior.